Albizia Forest Management System In The Madiun Distric - Indah Rekyani Puspitawati; Anang Susanto (International Journal of Science and Environment (IJSE), 2022)
communities in using natural resource areas. This study aims to determine the advantages of the agroforestry system, which is a mixture of albizia and mountain rice.  The agroforestry system gave the best growth of albizia  after three years.  The mean Annual Increment diameter and height of 3-year-old albizia plants in agroforestry systems were 14.02 cm and 7.19 m, respectively. The agroforestry system is also believed to reduce the number of forest damage because local people who originally stole forest wood have begun to be diverted to more productive planting activities with an intensification pattern. The involvement of local communities in business activities based on natural resource management in various forms is part of the concept of corporate social responsibility. The agroforestry system is superior to the intensive monoculture pattern because it can absorb more labor and increase the income of local communities, creating cooperation and togetherness between companies. Furthermore, an agroforestry system can reduce the number of forest and land fires because local communities, as arsonists, will help protect their land and crops.